Optimizing Transportation Costs for Distribution of Food Products Using the Modified Distribution (Modi) Method in Medan City (Case Study: Pt. Indomarco Adi Prima) - Farhan, Luthfi; Rakhmawati, Fibri (Information Technology and Science (ITScience), 2024)
Every company in the world always hopes for the maximum possible profit so that the company's life cycle runs well. For this reason, the company must be able to manage the costs used in such a way so that there is a gap between the company's expenses and income. PT. Indomarco Adi Prima is one of the companies operating in the food products sector which still finds it difficult to determine the right method for optimizing transportation costs. Therefore, this research aims to obtain optimal transportation costs at PT. Indomarco Adi Prima in the city of Palu using the Modified Distribution (MODI) method. The results of this research show that before implementing the Modified Distribution (MODI) method the transportation costs incurred by PT. Indomarco Adi Prima, which is IDR. 61,510,000 and the resulting transportation costs after using the Modified Distribution (MODI) method are IDR. 55,565,000. This shows that PT. Indomarco Adi Prima can optimize transportation costs for the distribution of food products in December 2023 with distribution cost savings of IDR. 5,945,000 or around 10.7%.